(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aims to examine the features of political discourse in Libyan theatrical texts and performances through analyzing the artistic and intellectual structure of dramatic texts and their relation to the development of this discourse. It also investigates the extent to which Libyan theatre was influenced by political authority and historical conditions during the period (1966–1976), while identifying whether it functioned as a free means of expression reflecting social and political reality or as a tool directed by official cultural policies, in addition to revealing the artistic mechanisms used to convey political discourse. The significance of the study lies in its academic contribution to enriching critical studies of Arab and Libyan theatre by exploring the relationship between theatre and political discourse in an under-researched period, as well as in developing tools for analyzing theatrical discourse. Practically, it highlights the role of theatre as a medium for expressing political and social issues. The study addresses the problem of understanding the nature of political discourse in Libyan theatre and its capacity to express itself between guidance and freedom during the studied period, raising the question of how this discourse manifested and the roles it played. It adopts a descriptive-analytical methodology to analyze theatrical texts and performances within Libya during (1966–1976). The study concludes that political discourse is an inherent element in Libyan theatre, expressed in both direct and symbolic forms, and that the National Theatre played a key role in organizing theatrical activity. However, administrative constraints, censorship, and limited resources hindered its development. The study recommends supporting specialized research, archiving theatrical works, encouraging comparative studies, and re-examining them using modern analytical approaches.